'A hidden disorder until the pieces fall into place' - a qualitative study of vaginal prolapse - Löfgren Mats; Persson Margareta; Pakbaz Mojgan; Mogren Ingrid (BMC, 2010)
Abstract Background Vaginal prolapse affects quality of life negatively and is associated with urinary, bowel, and sexual symptoms. Few qualitative studies have explored women's experiences of vaginal prolapse. The objective of the study was to elucidate the experiences of living with prolapse and its impact on daily life, prior to surgical intervention. Methods In-depth interviews were conducted with 14 women with vaginal prolapse, prior to surgical treatment. Recruitment of the informants was according to 'purposive sampling'. An interview guide was developed, including open-ended questions addressing different themes, which was processed and revised during the data collection and constituted part of a study-emergent design. Data were collected until 'saturation' was achieved, that is, when no significant new information was obtained by conducting further interviews. Interviews were audiotaped, transcribed verbatim, and analyzed according to manifest and latent content analysis. Results The theme defining the process of living with prolapse and women's experiences was labelled 'process of comprehension and action'. The findings constitute two categories: obstacles and facilitators to seeking health care. The category obstacles comprises six subcategories that define the factors restraining women from seeking health care: absence of information, blaming oneself, feeling ignored by the doctor, having a covert condition, adapting to successive impairment, and trivializing the symptoms and de-prioritizing own health. The category facilitators include five subcategories that define the factors promoting the seeking of health care: confirmation and support by others, difficulty in accepting an ageing body, feeling sexually unattractive, having an unnatural body, and reaching the point of action. Conclusion The main theme identified was the 'process of comprehension and action'. This process consisted of factors functioning as either obstacles or facilitators to seeking health care. The main obstacles described by the participants were lack of information and confirmation. The main facilitators constituted feeling sexually unattractive and impaired physical ability due to prolapse. Information on prolapse should be easily accessible, to improve the possibility for women to gain knowledge about the condition and overcome obstacles to seeking health care. Health care professionals have a significant role in facilitating the process by confirming and informing women about available treatment.